Penerapan Hidroterapi Dalam Upaya Menurunkan Tekanan Darah Penderita Hipertensi di Desa Mipitan Kelurahan Mojosongo - Monica Dhea Puspitasari; Mulyaningsih Mulyaningsih (Jurnal Anestesi, 2024)
Background: A person who is said to be hypertensive is a condition of someone who experiences an increase in high blood pressure that reaches a systolic number of more than 140 mmHg and a diastolic number of more than 90 mmHg. The prevalence of hypertension cases in the Surakarta City Health Office found an increase in the incidence of hypertension in 2023 reaching 67,355 cases. One of the Non-Pharmacological therapies that can be used is hydrotherapy. Purpose: This application describes a comparison of blood pressure developments before and after the application of hydrotherapy. Method: This application uses a case study of 2 respondents carried out for 6 consecutive days within a week with a therapy duration of 30 minutes at a temperature of 40 ° C. Results: The application of hydrotherapy to both respondents obtained the results of a comparison of developments before and after therapy in Mrs. S systolic blood pressure 20 MmHg diastolic 10 MmHg and in Mrs. M systolic blood pressure 22 MmHg diastolic 10 MmHg. Conclusion: The results of the study can be concluded that there is an effect of hydrotherapy on systolic and diastolic blood pressure in both respondents.